2018
DOI: 10.1002/ptr.6183
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl isothiocyanate inhibits colorectal cancer stem cells by suppressing Wnt/β‐catenin pathway

Abstract: Cancer stem cells (CSCs) are considered to play essential roles in the process of origination, proliferation, migration, and invasion of cancer, and their properties are regulated by Wnt/β-catenin pathway. Phenethyl isothiocyanate (PEITC) is a natural product obtained from cruciferous vegetables with anticancer activities. The present study aimed to investigate the inhibitory effect and the underlying mechanisms of PEITC on colorectal CSCs. In this study, we found that PEITC can significantly reduce the size a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 35 publications
(36 reference statements)
0
37
1
Order By: Relevance
“…Several other natural products have been found to down-regulate the expression of β-catenin, including resveratrol ( Mitani et al., 2014 ; Mineda et al., 2019 ), phenethyl isothiocyanate (PEITC) ( Chen et al., 2018 ), gigantol ( Yu et al., 2018 ), polysaccharide from Phellinus linteus ( Song et al., 2011 ), and riccardin D ( Liu et al., 2012 ). Among them, resveratrol and PEITC are two well-documented dietary anticancer chemopreventive compounds with multiple molecular targets ( Mitani et al., 2014 ; Chen et al., 2018 ; Mineda et al., 2019 ). Recent studies have shown that resveratrol and PEITC also inhibit the β-catenin signaling; however, the importance of β-catenin in their anticancer activity is yet to be determined ( Mitani et al., 2014 ; Chen et al., 2018 ; Mineda et al., 2019 ).…”
Section: Natural Product Inhibitors Of β-Catenin Signaling Pathwaymentioning
confidence: 99%
“…Several other natural products have been found to down-regulate the expression of β-catenin, including resveratrol ( Mitani et al., 2014 ; Mineda et al., 2019 ), phenethyl isothiocyanate (PEITC) ( Chen et al., 2018 ), gigantol ( Yu et al., 2018 ), polysaccharide from Phellinus linteus ( Song et al., 2011 ), and riccardin D ( Liu et al., 2012 ). Among them, resveratrol and PEITC are two well-documented dietary anticancer chemopreventive compounds with multiple molecular targets ( Mitani et al., 2014 ; Chen et al., 2018 ; Mineda et al., 2019 ). Recent studies have shown that resveratrol and PEITC also inhibit the β-catenin signaling; however, the importance of β-catenin in their anticancer activity is yet to be determined ( Mitani et al., 2014 ; Chen et al., 2018 ; Mineda et al., 2019 ).…”
Section: Natural Product Inhibitors Of β-Catenin Signaling Pathwaymentioning
confidence: 99%
“…Immunoblotting analysis was performed as described previously 38 . In brief, 40 μg of total proteins in 15 μL were subject to 7.5-10% SDS-PAGE, transferred to nitrocellulose filter membrane (Millipore, Billerica, MA, USA), exposed to the antibodies, and detected by Chemiluminescence western blotting reagents (Cell Signaling Technology, Danvers, MA).…”
Section: Immunoblotting Analysismentioning
confidence: 99%
“…In addition, the levels of β-catenin, a transcription factor that contributes to the expression of many CSC genes [31], were significantly reduced after incubation with PEITC (Figure 7a). reported that PEITC significantly inhibits sphere formation in colorectal cancer by targeting the Wnt/β-catenin pathway [54]. Importantly, incubation with PEITC promoted ROS production ( Figure 5b) and decreased GSH levels (Figure 5c).…”
Section: Discussionmentioning
confidence: 82%
“…Our results showed that PEITC could eliminate the CSC population in MDA-MB-231/IR cells, as evidenced by the significant inhibition of mammosphere formation, the CD44 + /CD24 − population, and ALDH activity (Figure 6a-c). PEITC has been reported to target CSC compartments in a variety of cancers, including cervical cancer [53], colon cancer [33], colorectal cancer [54], and HeLa cancer cells [10]. Recently, Koschorke et al (2019) found that PEITC can target HER-2 positive BCSCs, and this effect was enhanced in combination with trastuzumab therapy [55].…”
Section: Discussionmentioning
confidence: 99%